A review of recent advances in electrochemically modulated extraction methods - Collins, C.; Arrigan, Damien (Springer-Verlag, 2009)
The use of electrochemistry and electrical behavioras a control and manipulation factor in analyte extractions isreviewed. Electromodulated extractions of ionic and neutralanalytes are possible using this general approach. Extractionsbased on solid–liquid, liquid–liquid and membrane behaviorshave been demonstrated and reported together with analyteextractions from real matrices and interfacing with instrumentaldetection methods. The electromodulation strategy offersgreat opportunities for selectivity in sample preparation.